Britannia and the bear : the Anglo-Russian intelligence wars ; 1917 - 1929 - Madeira, Victor (History of British intelligence, 2014)
Decades before the Berlin Wall went up, a Cold War had already begun raging. But for Bolshevik Russia, Great Britain - not America - was the enemy. Now, for the first time, Victor Madeira tells a story that has been hidden away for nearly a century. Drawing on over sixty Russian, British and French archival collections, this book offers a compelling new narrative about how two great powers of the time did battle, both openly and in the shadows. By exploring British and Russian mind-sets of the time this book traces the links between wartime social unrest, growing trade unionism in the police and the military, and Moscow's subsequent infiltration of Whitehall. As early as 1920, Cabinet ministers were told that Bolshevik intelligence wanted to recruit university students from prominent families destined for government, professional and intellectual circles. Yet despite these early warnings, men such as the Cambridge Five slipped the security net fifteen years after the alarm was first raised. This book tells the story of Russian espionage in Britain in these critical interwar years and reveals how British Government identified crucial lessons but failed to learn many of them. The book underscores the importance of the first Cold War in understanding the second, as well as the need for historical perspective in interpreting the mind-sets of rival powers